Just a Shadow? The Role of Radical Right Parties in the Politicization of Immigration, 1995–2009 - Meyer, Sarah (2015)
The paper explores the role of radical right parties in the politicization of immigration. In scholarly literature, radical right parties are viewed as the owners of the immigration issue and as drivers of its politicization. Against this prevalent view, we argue that the significance of radical right parties in politicizing immigration is overrated: (1) Radical right parties only play a subordinate role in the politicization of immigration, whereas the contribution of mainstream parties to raising issue salience has been underestimated; (2) the politicization of immigration is not related to radical right strength in the party system. The findings are based on media data from a comparative project on public claims-making on immigration in Western European countries (SOM, Support and Opposition to Migration). We discuss our findings in comparison to the relevant literature and suggest avenues for further research.